Tracing terrestrial DOC in the Baltic Sea—A 3‐D model study. Issue 2 (2nd February 2016) - Fransner, Filippa; Nycander, Jonas; Mörth, Carl‐Magnus; Humborg, Christoph; Markus Meier, H. E.; Hordoir, Robinson; Gustafsson, Erik; Deutsch, Barbara
Abstract: The fate of terrestrial organic matter brought to the coastal seas by rivers and its role in the global carbon cycle are still not very well known. Here the degradation rate of terrestrial dissolved organic carbon (DOCter ) is studied in the Baltic Sea, a subarctic semienclosed sea, by releasing it as a tracer in a 3‐D circulation model and applying linear decay constants. A good agreement with available observational data is obtained by parameterizing the degradation in two rather different ways: one by applying a decay time on the order of 10 years to the whole pool of DOCter and one by dividing the DOCter into one refractory pool and one pool subject to a decay time on the order of 1 year. The choice of parameterization has a significant effect on where in the Baltic Sea the removal takes place, which can be of importance when modeling the full carbon cycle and the CO2 exchange with the atmosphere. In both cases the biogeochemical decay operates on time scales less than the water residence time. Therefore, only a minor fraction of the DOCter reaches the North Sea, whereas approximately 80% is removed by internal sinks within the Baltic Sea. This further implies that DOCter mineralization is an important link in land‐sea‐atmosphere cycling of carbon in coastal and shelf seas that are heavily influenced by riverine DOC. Key Points: The removal of terrestrial DOC in the Baltic Sea is studied with a 3‐D model Eighty percent of the riverine input of DOC is removed within the Baltic Sea Freshwater residence time is an important factor regulating the export of DOC to the open ocean